Model Pengambilan Keputusan Berwisata - Hari Rachmadi (Media Wisata, 2016)
The travelling decision model reflects the Characteristics and type of travel. It differentiates and compares the tendencies of decision-making behaviour in different situational. The Travelling decision is established by the different motives of each individualand group. Where the situational factor affects the behaviour of decision making. Most of the decision-making processes require the involvement of behaviour in using the information like in contemporary decision making. one of the examples is the decision to travel. The logical decision making is the decision made through clear steps that reflects the different characteristics of behaviour in specific decision situations which the values are related and chosen tourist destination are suitable and desirable